2019
DOI: 10.1177/2309499019877517
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency and deficiency of vitamin D in elderly patients with fragility fractures of the hip in the Japanese population

Abstract: Background: Data of vitamin D sufficiency in Asian patients with osteoporotic fragility hip fractures are limited. This study aimed to obtain data from the Japanese population. Methods: Patients aged 60 years or older with hip fractures were prospectively enrolled. Serum 25-hydroxyvitamin D (25(OH)D) levels were measured. Levels were compared between patients receiving and not receiving treatment for osteoporosis, those with and without previous contralateral hip fractures, and those with femoral neck versus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Vitamin D deficiency is particularly prevalent in older adults with hip fracture, but its prevalence varies among the studies conducted. In the present study, over half of the patients were deficient in vitamin D. Table 4 summarizes the results of studies conducted in the last two decades regarding the prevalence of vitamin D deficiency in older adults with hip fracture (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 70%
“…Vitamin D deficiency is particularly prevalent in older adults with hip fracture, but its prevalence varies among the studies conducted. In the present study, over half of the patients were deficient in vitamin D. Table 4 summarizes the results of studies conducted in the last two decades regarding the prevalence of vitamin D deficiency in older adults with hip fracture (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 70%
“…This implies that sunlight exposure may play a role in the prevention of fracture independent of serum 25-hydroxyvitamin D. A few studies support this finding. 8 24 One study showed no correlation between UV index and serum 25-hydroxyvitamin D levels in older adults with hip fracture. 24 Furthermore, sunlight exposure may have a direct effect on bone or bone metabolism apart from vitamin D synthesis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 24 One study showed no correlation between UV index and serum 25-hydroxyvitamin D levels in older adults with hip fracture. 24 Furthermore, sunlight exposure may have a direct effect on bone or bone metabolism apart from vitamin D synthesis. Research has indicated that cumulative increases in sun exposure, independent of vitamin D concentration, have a protective effect against fracture in older females 8 and against osteoporotic fracture in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Despite severe vitamin D deficiency below 30 nmol/l being present in the majority of hip fracture patient, only 10% of hip fracture patients had any vitamin D supplementation on admission [ 12 ]. The prevalence of vitamin D deficiency is even higher in patients with previous contralateral hip fractures as compared to those without [ 44 ], suggesting that most surgeons do not prescribe vitamin D to fractured patients. Patients with osteoporotic fractures and/or musculoskeletal symptoms, which can be potentially improved by vitamin D treatment or need the correction of vitamin D deficiency prior to specific treatment, should have serum 25(OH)D levels measured [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…2). Many studies in patients with hip fractures and an average age of around 80 years and over have reported a prevalence of serum 25(OH)D below 50 nmol/l ranging between 34 and 80%, even if mean values are around 40 to 50 nmol/l [12,14,[40][41][42][43][44][45][46][47][48] (Table 1). A high prevalence of vitamin D deficiency was also observed among 219 orthopedic patients presenting with vertebral fragility fractures [49] as well as among 93 patients with pelvic insufficiency fractures [50].…”
Section: Prevalence Of Vitamin D Deficiency In Patients With Osteoporotic Fracturesmentioning
confidence: 99%